Pengembangan Pendidikan Islam Berbasis Multikultural (Studi pada Pondok Pesantren Al-Qodiri dan Al-Ghazali Jember): Development of Multicultural-Based Islamic Education (A Study at Al-Qodiri and Al-Ghazali Islamic Boarding Schools in Jember) - Zain, Hefni (Fenomena, 2014)
Amidst societal awareness of plurality, the development of multicultural education continues to expand to various places, including several Islamic boarding schools in the Jember region, particularly Al-Qodiri and Al-Ghazali Islamic boarding schools. Over the past five years, these two boarding schools have developed multicultural education, which emphasizes the importance of respecting plurality and acknowledging pedagogical equality for all individuals who have the same right to receive educational services, regardless of their ethnicity, social status, religion, or gender. This research is based on the general question: What is the strategy for developing multicultural-based Islamic education at Al-Qodiri and Al-Ghazali Islamic boarding schools in Jember? To address this general question, the research aims to answer three specific questions: (1) How is the implementation of multicultural-based Islamic education development at these two institutions? (2) What steps have the leaders of these institutions taken to develop multicultural-based Islamic education? (3) What are the opportunities and obstacles in developing multicultural-based Islamic education at these two institutions? Dalam kesadaran masyarakat akan pluralitas, pengembangan pendidikan multikultural terus merambah ke berbagai tempat, termasuk beberapa pondok pesantren di wilayah Jember, khususnya Pondok Pesantren Al-Qodiri dan Al-Ghazali Jember. Selama lima tahun terakhir, kedua pondok pesantren tersebut telah mengembangkan pendidikan multikultural, yaitu pendidikan yang menekankan pentingnya penghormatan terhadap pluralitas dan pengakuan kesetaraan pedagogis terhadap semua orang yang memiliki hak yang sama untuk memperoleh layanan pendidikan, apa pun etnis, status sosial, agama, dan jenis kelaminnya. Penelitian ini didasarkan pada pertanyaan umum: Bagaimana strategi pengembangan pendidikan Islam berbasis multikultural di Pondok Pesantren Al-Qodiri dan Al-Ghazali Jember? Untuk memahami pertanyaan umum tersebut, penelitian ini berusaha menjawab tiga pertanyaan spesifik: (1) Bagaimana implementasi pengembangan pendidikan Islam berbasis multikultural di kedua lembaga tersebut? (2) Bagaimana langkah-langkah pimpinan kedua lembaga dalam mengembangkan pendidikan Islam berbasis multikultural? (3) Apa saja peluang dan hambatan dalam pengembangan pendidikan Islam berbasis multikultural di kedua lembaga tersebut?